Efficiency wages: Variants and implications - Ekkehart Schlicht (IZA World of Labor, 2016)
Higher wages increase labor costs but also improve the productivity of the labor force in several ways. If firms take this into account and set their wages accordingly, the resulting wages could fail to adjust demand and supply but may induce phenomena like over-education, discrimination, regional wage differentials, and a tendency for larger firms to pay higher wages. All these phenomena are quantitatively important and well-established empirically. Efficiency wage theory provides an integrated theoretical explanation rather than a sundry list of reasons, and offers an efficiency argument for progressive income taxation.
Keywords: J31; J63; 330; efficiency wages; selection wages; turnover; morale; discipline